LEISHMANIOSE TEGUMENTAR AMERICANA: FAUNA FLEBOTOMÍNICA EM ÁREAS DE TRANSMISSÃO NO MUNICÍPIO DE UBERLÂNDIA, MINAS GERAIS, BRASIL - Lemos, Jureth Couto; Lima, Samuel do Carmo; Costa, Márcia Batista da; Magalhães, Maria José (Caminhos de Geografia, 2001)
From October 7th 1999 to January 18th 2001 studies have been developed on thephlebotominic fauna in areas of transmission of american cutaneous leishmaniosis in the County of Uberlândia, Triângulo Mineiro Region in Minas Gerais State, Brazil, from a survey on files of patients who contracted the disease in the County. In order to capture the sand flies it has been used traps of the Shannon type, fed by two 100 Watt gas lights, and lighted-up traps of the type CDC (Center of Disease Control), fed by two 12 Volt batteries. 8657 sand flies have been captured and identified, which are from two genders and 13 species. One Brumptomyia specie and 12 Lutzomyia species. The greatest amount of species found was from the Lutzomyia intermedia, with 8602 sand flies, followed by the Lutzomyia lutziana with 10, Lutzomyia sallesi with 08, Lutzomyia whitmani with 06, Lutzomyia shannoni, termitophila and lenti with 03, Lutzomyia sp. (unidentified species), Lutzomyia sordellii and Lutzomyia cortellezzi with 02 sand flies each, Lutzomyia renei and Lutzomyia longipennis with 01 sand flies each and the Brumptomyia sp. With 14 sand flies. In the the Shannon type trap it has been captured 7606 and in the CDC type trap 1051. Regarding sex, it has been identified 2335 male and 6322 female sand flies.